PERCEPTIONS OF PROSPECTIVE TAXPAYERS AND TAXPAYERS ON THE ETHICS OF TAX EVASION IN SALATIGA - Nelphy Bryan Abrahams; Ari Budi Kristanto (Universitas Airlangga, 2016)
A number of taxpayers are still committing tax evasion. This was done for the reasons, among others, dissatisfaction with the tax system, unfair tax practices and tax discrimination treatment. This study was conducted to explore the perception of taxpayers and prospective taxpayers on tax evasion behavior, specifically from the point of view of the taxation system, tax justice and discrimination in taxation. This study uses a survey method on the respondents. Taxpayer respondents in this study are individual taxpayers with income from work and business. The prospective taxpayers are obtained from students of management and accounting study programs. The research data were then analyzed using descriptive statistical analysis techniques. The results of this study found that in general, respondents do not agree that tax evasion is an ethical act, even though the tax system does not work well, there is no justice and discrimination occurs in taxation practices. Based on the findings of this study, it can be concluded that in general taxpayers and prospective taxpayers have a negative perception of tax evasion. This is a capital for the government in improving tax compliance.